The Meaning of Audience’s Reception on Da’wah Messages in the Gus Iqdam Youtube Channel: (A Reception Study On Majelis Taklim Al Muhsinin) - kurniawan, jihan; Safitri, Reza (Sahafa Journal of Islamic Communication, 2024)
This study analyzes the audience's interpretation of da'wah messages on the Gus Iqdam YouTube channel, focusing on the Majelis Taklim Al Muhsinin congregation. Using a qualitative reception analysis method, the research reveals that audience interpretations vary, influenced by their social backgrounds and understanding of Islamic teachings. The findings show that YouTube as a platform significantly enhances the reach of da'wah, despite challenges in maintaining message relevance. This study emphasizes the importance of Da'wah Communication and Spiritual Communication approaches to explore the emotional and religious dimensions of Gus Iqdam's da'wah, which is adaptive and responsive in engaging diverse audiences in the digital era.